SuperAgent: A Customer Service Chatbot for E-commerce Websites - Cui, Lei; Wei, Furu; Huang, Shaohan; Tan, Chuanqi; Duan, Chaoqun; Zhou, Ming (ACL 2017, 2017)
Conventional customer service chatbots are usually based on human dialogue, yet significant issues in terms of data scale and privacy. In this paper, we present SuperAgent, a customer service chatbot that leverages large-scale and publicly available e-commerce data. Distinct from existing counterparts, SuperAgent takes advantage of data from in-page product descriptions as well as user-generated content from e-commerce websites, which is more practical and cost-effective when answering repetitive questions, freeing up human support staff to answer much higher value questions. We demonstrate SuperAgent as an add-on extension to mainstream web browsers and show its usefulness to user's online shopping experience.